A Systematic Literature Review: Fuel Subsidy and Consumer Environmental Awareness in Urban Road Transport - Nor Aziedah, Mhd Noh; Juliana, Mohd Abdul Kadir; Ahmad Razi, Ramli; Rosita, Hamdan (2021)
Using a systematic literature review, weexplore fuel subsidies and consumer environmental awarenessamong users in urban road transport.Fuel subsidies given by the government to the public have to some extent brought them to moreusing own transport as the fuel cost is now cheaper.A growingnumber of vehicles and usage in the urban road transport sector worldwide has increasedCO2 emissionsand impact on environment. The misalignment of benefits from the implementation offossil fuel subsidies and highemissions has grown attention to limit global warming since the Paris Agreement 2015 was signed. Nonetheless, consumerenvironmentalawarenessis interesting to bring forward for future research.